Avaliação da agradabilidade facial em indivíduos do padrão face longa - Goulart, Maiara da Silva (2017)
Objective: The present study aims to determine orthodontist and layperson's perception about facial aesthetics of long face pattern sample. Materials and Methods: The sample consisted of 64 frontal photos, of long face individuals (10 to 15 years old), diagnosed through morphological evaluation of the face and confirmed by the facial index. Likert scale was used to determine orthodontist (22) and layperson's (22) perception about facial aesthetics.The chi-square and the proportions test were used for the comparison between the examiners regarding the classification in each degree of pleasantness, adopting a significance level of 5%. Results: For orthodontists and laypeople most of the individuals were considered acceptable: 36.4% and 40.3% respectively. Subjects classified as aesthetic unpleasant were 1/3 of the sample: 7.8% very unpleasant and 22.9% unpleasant for orthodontists and 6.7% and 22.2% for laypeople. The facial structures most cited as responsible for unpleasantness were the lack of lip sealing followed by the incisor exposition. The increase of the lower third of the face for orthodontists and eyes for the laypeople were the third most cited unpleasant characteristic. Conclusions: For the evaluators 2/3 of the long face sample were considered acceptable, pleasant and very pleasant. Layperson's opinion shared with the orthodontists, that only 1/3 of long face patients were considered unpleasant